Peran dan Implementasi Etika Bisnis dalam Membangun Kepercayaan dan Kepuasan Konsumen di Era Persaingan Usaha Modern - Hartono, Ardhit Wiro Hartono; Faried , Ade Achmad; Dina, Nur; Dara, Satria Danur (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
In today's highly competitive business environment, business ethics serve as a crucial foundation for building consumer trust and satisfaction. This study aims to analyze the role and implementation of business ethics, both from conventional and Islamic perspectives, in strengthening the relationship between producers and consumers using a literature review approach. The method used is a literature review based on ten primary sources, including relevant books and journals. The findings indicate that the application of ethical principles, such as honesty, social responsibility, transparency, and Sharia-based values, positively contributes to customer loyalty and satisfaction, particularly in modern business sectors such as laundry services and cafés. This research confirms that ethics are not merely a moral obligation but also a key strategy for achieving sustainable competitive advantage.